Content Analysis of Netizens’ Comments on the Bullet Effect and Boomerang Effect in Ustadz Hanan Attaki’s Da'wah on Instagram - N, Nasichah; Syair, Najwa Nur; Azizah, Naila Nur; Maulani, Nova Aprilia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The transformation of social media into a comment section serves as a platform for public reception of religious messages. The popular messages of Ustadz Hanan Attaki have sparked various responses, demonstrating the potential for messages to be accepted (bullet effect) or rejected (boomerang effect). The dualistic nature of this phenomenon is highly contradictory when it comes to determining the effectiveness of religious communication in the digital space. This study aims to discover and examine patterns of boomerang and bullet effect acceptance in audience (mad'u) comments in response to Ustadz Hanan Attaki's religious content. Using a qualitative research design with descriptive comment analysis, data in the form of audience reactions on social media was collected using non-participatory observation and documentation techniques. The data were analyzed using qualitative content analysis to categorize and interpret the nuances of acceptance and rejection. The results showed that the bullet effect was led by comments of emotional support and agreement with motivational themes, while the boomerang effect occurred from comments that questioned the contextual interpretation of religious teachings or the personal aspects of the da'i. Effective da'wah communication occurs when the message is in line with the audience's needs. This study contributes to mapping the challenges of digital dakwah reception, emphasizing the active role of the audience in creating meaning from messages.